Diagnosis of Cardiac Abnormalities in Muscular Dystrophies - Elisabeta Bădilă; Iulia Ioana Lungu; Alexandru Mihai Grumezescu; Alexandru Scafa Udriște (Medicina, 2021)
Muscular disorders are mainly characterized by progressive skeletal muscle weakness. There are several aspects that can be monitored, which are used to differentiate between the types of muscular disorders, ranging from the targeted muscle up to the mutated gene. An aspect that holds critical importance when managing muscular dystrophies is that most of them exhibit cardiac abnormalities. Therefore, cardiac imaging is an essential part of muscular disorder monitoring and management. In the first section of the review, several cardiac abnormalities are introduced; afterward, different muscular dystrophies’ pathogenesis is presented. Not all muscular dystrophies necessarily present cardiac involvement; however, the ones that do are linked with the cardiac abnormalities described in the first section. Moreover, studies from the last 3 years on muscular disorders are presented alongside imaging techniques used to determine cardiac abnormalities.